Characteristics of Pindang Boiling Water and Its Use to Produce Antioxidative Peptides through Trypsin Hydrolysis - Dali, Faiza A.; Nurjanah, Nurjanah; Lioe, Hanifah N.; Suhartono, Maggy T. (:Agency for Marine and Fisheries Research and Human Resources, Indonesia, 2024)
Pemindangan is a traditional fish processing method in Indonesia, where fish are preserved by boiling in saltwater. This process results in a liquid as a by-product, which is often discarded without any further processing. The liquid contains a substantial amount of protein, reaching 1.04±0.03 mg/mL, which make it a potential source of bioactive peptides. This study aimed to produce bioactive peptides from pindang liquid which was hydrolysed by enzymes isolated from skipjack viscera. The hydrolysates were prepared by using extracted trypsin, which was also from a fish by-product. The trypsin-assisted hydrolysis was carried out at a temperature 60 °C and pH 8.0, while for the semi-purified trypsin, the process was run at 50 °C and pH 8.0. The hydrolysis time was operated at different periods of 15, 30, and 60 min. The results showed that the pindang liquid dominantly contained hydrophobic amino acids and the hydrolysate was still rich in protein content ranging from 0.56 to 0.65 mg/mL. Furthermore, hydrolysis time significantly influenced antioxidant activity of the peptide. The best antioxidant activity was shown at hydrolysis time of 15 min by crude extract enzymes, resulting in antioxidant activity of 0.90±0.01 mg ascorbic acid equivalent antioxidant capacity (AEAC)/mg protein and reducing power of 4.49±0.60 mg trolox equivalent antioxidant capacity (TEAC)/mg protein. Hydrolysis by using semi-purified trypsin showed antioxidant activity equivalent to 0.73±0.05 mg AEAC/mg protein and reducing power 6.54±0.34 mg TEAC/mg protein. Overall, the results revealed the conversion of pindang liquid into bioactive peptides showing antioxidant activity, and therefore, they might be potentially developed as functional foods.